Reversible Lectin Binding to Glycan-Functionalized Graphene - Koukalová, Tereza; Kovaříček, Petr; Bojarová, Pavla; Guerra, Valentino L P; Vrkoslav, Vladimír; Navara, Lukáš; Jirka, Ivan; Cebecauer, Marek; Křen, Vladimír; Kalbáč, Martin (International journal of molecular sciences, 2021)
The monolayer character of two-dimensional materials predestines them for application as active layers of sensors. However, their inherent high sensitivity is always accompanied by a low selectivity. Chemical functionalization of two-dimensional materials has emerged as a promising way to overcome the selectivity issues. Here, we demonstrate efficient graphene functionalization with carbohydrate ligands-chitooligomers, which bind proteins of the lectin family with high selectivity. Successful grafting of a chitooligomer library was thoroughly characterized, and glycan binding to wheat germ agglutinin was studied by a series of methods. The results demonstrate that the protein quaternary structure remains intact after binding to the functionalized graphene, and that the lectin can be liberated from the surface by the addition of a binding competitor. The chemoenzymatic assay with a horseradish peroxidase conjugate also confirmed the intact catalytic properties of the enzyme. The present approach thus paves the way towards graphene-based sensors for carbohydrate-lectin binding.
Keywords: polysacharidy; lektiny; Protein Binding; 2D materials; Graphite; Horseradish Peroxidase; grafit; vazba proteinů; wheat germ agglutinin; kvarterní struktura proteinů; Polysaccharides; Protein Structure, Quaternary; křenová peroxidasa; sensor; Lectins; graphene; carbohydrate